PENGAWASAN DPRD PROVINSI DKI JAKARTA DALAM PROGRAM PENATAAN KAWASAN PERMUKIMAN KUMUH DI JAKARTA SELATAN TAHUN 2022-2024 - Estu Samboga; Dadan Kurniansyah (LPPM Universitas Abdurrab, 2025)
The slum area restructuring program is one of the efforts of the DKI Jakarta Provincial Government to solve many problems in the city of Jakarta, one of which is the problem in residential areas. The Jakarta Provincial Government is trying to accelerate the arrangement of this slum area to welcome Jakarta as a Global City and the National Economic Center. However, in its implementation, problems are still found in its implementation, such as the number of slums that are not recorded, the existence of invalid data in the slum RW reporting system. Based on these problems, more in-depth research is needed to provide a factual picture in the field. This study aims to identify the supervision of the DKI Jakarta Provincial DPRD in the slum area arrangement program in South Jakarta in 2022-2024. This study uses a descriptive qualitative research method with data collection techniques through observation, interviews, and documentation. The data analysis techniques are in the form of data collection, data reduction, data presentation, and data verification. And the informant determination technique in this study uses the purposive sampling technique. The results of the study revealed that the supervision carried out by the DKI Jakarta Provincial DPRD was quite optimal, this was proven by the supervision carried out directly and indirectly. In the findings of the DKI Jakarta Provincial DPRD in the implementation standard discussion, it is in accordance with the plan, but there are several things that need to be evaluated and need improvement actions. The corrective action is in the form of a revision of the regulation of the slum area arrangement program. it's just that there is no determination of implementation measurements at the DKI Jakarta Provincial DPRD so that there is no scheduled supervision implementation.